Karakteristik Pasien Tonsilitis Pada Anak Usia 5-12 Tahun di RSPBA Bandar Lampung Tahun 2020 - Renita Dwi Rahayu; Tan’im Arief; Selvia Anggraeni (ARTERI : Jurnal Ilmu Kesehatan, 2021)
Tonsillitis is a disease that is often experienced by a person, especially often occurs in children. Based on a survey from the Indonesian Ministry of Health in 2012, the incidence of tonsillitis in Indonesia reached around 23%. Acute tonsillitis that is not properly treated can cause chronic tonsillitis, therefore it is important to know the characteristics of tonsillitis symptoms in order not to develop into chronic tonsillitis. Tonsillitis is an inflammation of the tonsils caused by infection with the Streptococcus group of bacteria or viruses which can be acute or chronic. Symptoms that often appear in tonsillitis are sore throat, difficulty swallowing and when it reaches chronic it can block the respiratory tract. The purpose of this study was to determine the characteristics of tonsillitis patients in children aged 5-12 years at Rspba Bandar Lampung in 2020. The research method in this study was cross-sectional. It is known that the results of the study of tonsillitis patients in children, the most common symptom of which was pain during swallowing (40.5%), tonsillitis patients in children were often found in T2-T2 sizes (37.8%), tonsillitis patients in children were often experienced. by men (71.1%). tonsillitis patients in children are often experienced by ages 7-8 years (48.6%), the incidence of tonsillitis cases is 8.34%, the prevalence of tonsillitis cases in children aged 5-12 years is 41.1%, in children aged 5 -12 years have a lot of chronic tonsillitis. The characteristics found in tonsillitis patients aged 5-12 years, namely swallowing pain, widening of the T2-T2 tonsil size, mostly experienced by men and often occurs at 7-8 years of age, the incidence is 8.34%, prevalence in children. age 5-12 years as much as 41.1% and many children have chronic tonsillitis.